Cilostamide affects in a concentration and exposure time-dependent manner the viability and the kinetics of in vitro maturation of caprine and bovine oocytes. (February 2019) - Correia, H.H.V.; Vieira, L.A.; Mielgo, C.M.; Paes, V.M.; Alves, B.G.; Silva, J.R.V.; Wheeler, M.B.; Rodrigues, A.P.R.; Figueiredo, J.R.
Abstract: This study investigated: 1) the kinetics of oocyte chromatin configuration during in vitro maturation (IVM) of caprine and bovine oocytes; and 2) the effect of in vitro pre-maturation (IVPM) with cilostamide with or without association of the follicular wall (FW) on the same parameters. In experiment I, cumulus-oocyte complexes (COCs) were cultured in vitro in a standard maturation medium for 6, 12, 18 or 30 h. For experiment II, the COCs were cultured for 30 h, either in a standard IVM medium or in IVPM containing cilostamide (10 or 20 μM) and FW alone or in combination, for 6 or 12 h before the onset of maturation. The MII rate was similar (P > .05) between 18 and 30 h of maturation, both of which were higher (P < .05) than 6 and 12 h IVM in both species (Experiment I). Contrary to caprine, all IVPM treatments presented a higher (P < .05) percentage of bovine oocytes arrested at the GV stage than the control treatment after 6 h of culture. The percentage of MII oocytes after 30 h (IVPM+IVM) of culture in bovine oocytes treated with 10 μM cilostamide associated with FW and FW alone cultured for 6 h presented MII percentages similar to the control. However, in caprine, these treatments significantly reduced the percentages of MII in relation to the control treatment (Experiment II). In conclusion, the combination of concentration-exposure time to cilostamide during IVPM delayed meiotic progression in bovine after 6 and 12 h of culture. However, overall the culture period (IVPM+IVM) influenced the oocyte chromatin configuration and kinetics in both species. Highlights: The combination (concentration-exposure time) to cilostamide during IVPM influenced oocyte chromatin configuration after IVM. Cilostamide impacts differently the kinetics of oocyte in vitro maturation in caprine and bovine. Oocyte exposure to cilostamide + FW in bovine caused a temporary blockage and further yielded MII rates similar to control.